MSC virtual e-abstract (OCL-02) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Falls after stroke at the University of Malaya Medical Centre falls clinic. Outcomes of thrombolysis therapy for acute ischemic stroke in a non-neurologist government hospital in northern region of Malaysia. Acute stroke unit of Seberang Jaya Hospital – Taking baby steps. Demographic and characteristics of acute stroke registry, Hospital Seberang Jaya (ASTRO-HSJ). Assessing white matter hyperintensities and neurocognitive profile in apparently asymptomatic individuals using graphical measurement assessment. Survey on post-stroke care services after discharge from Hospital Taiping. Exploring the utilization of animal-assisted intervention for individuals undergoing inpatient stroke rehabilitation.